Serotonin-related Mechanisms in the Etiology and Pharmacotherapy of Social Phobia, A Review: Serotonin and Social Phobia: Serotonin and Social Phobia - Arjmandi Ghandashtani, Malihe; Poudineh, Sahar; Sarlak, Alireza; Poudineh, Maryam (Galen Medical Journal, 2023)
Social anxiety disorder (SAD), known as social phobia, is considered a prevalent psychiatric disorder characterized by a constant fear of social positions. Frequently, social phobia occurs with other mental disorders including depression and substance abuse conditions. Although SAD is considered one of the most common types of mental disorders, proper management may be compromised in recurrent psychiatric comorbidity due to clinicians’ focus on secondary complications. Moreover, despite the description of social phobia as a polygenic and complex condition, few altered genetic and epigenetic factors are identified as causative agents. Over the past decades, several studies have suggested polymorphisms in serotonergic and dopaminergic-related genes as the etiology of social phobia. Serotonin, on the other hand, as a necessary neurotransmitter in the central nervous system (CNS), is involved in a variety of disease processes including social phobia. Nevertheless, the exact mechanism of serotonin-dependent development of the disease and the efficacy of suggested pharmacotherapies are not fully understood. The current study aimed to review the serotonin-dependent mechanisms by which SAD develops and discuss the current suggested strategies that are based on serotonin metabolism.